2017
DOI: 10.1007/s13197-017-2924-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of volatile compound markers during the ripening and senescence of lulo (Solanum quitoense Lam.)

Abstract: Lulo ( Lam.) is an exotic fruit cultivated in Colombia. During ripening and senescence, this climactic fruit undergoes biochemical processes that produce the volatiles responsible for its aroma. This study aimed to evaluate the changes in the volatile content during the ripening and senescence of lulo. Analysis of the volatile composition of lulo harvested in each of its five ripening stages and during its senescence time when stored at 18 ± 2 °C was performed using HS-SPME with GC-MS. Throughout ripening, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The lulo fruit has a sweet and acidic taste and is highly regarded for its pleasant aroma and flavor which result from a complex mixture of volatile compounds that include methyl and ethyl esters and glycoside derivatives (Brunke et al, 1989;Forero et al, 2015Forero et al, , 2016Corpas-Iguarán et al, 2018). Lulo is also rich in fiber, citric acid, calcium, phosphorus, niacin, thiamin, riboflavin, and vitamins A and C and different antioxidants (Huyskens-Keil et al, 2001;Gancel et al, 2008;Vasco et al, 2008;Acosta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The lulo fruit has a sweet and acidic taste and is highly regarded for its pleasant aroma and flavor which result from a complex mixture of volatile compounds that include methyl and ethyl esters and glycoside derivatives (Brunke et al, 1989;Forero et al, 2015Forero et al, , 2016Corpas-Iguarán et al, 2018). Lulo is also rich in fiber, citric acid, calcium, phosphorus, niacin, thiamin, riboflavin, and vitamins A and C and different antioxidants (Huyskens-Keil et al, 2001;Gancel et al, 2008;Vasco et al, 2008;Acosta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The composition and abundance of aroma volatiles are linked with the fruit maturity and level of ripeness. Studies have shown differences in volatile composition in the different ripening stages of bunch grapes [17], raspberries [18], bananas [19], lulos [20], figs [21], and muskmelons [22]. However, no research has been conducted to understand the effect of berry ripeness on the aroma volatile composition of muscadines.…”
Section: Introductionmentioning
confidence: 99%